Sahiron Syamsuddin’s Contributions to the Methodological Discourse of Al-Qur’an Interpretation in Indonesia - Zulfa, Imarotuz (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2023)
This paper aims to analyze the interpretive methodology of the Al-Qur’an as proposed by Sahiron Syamsuddin, and its relevance in the discourse surrounding Al-Qur’an interpretation methodology in Indonesia. Employing a qualitative methodology with a library research model, this study primarily relies on Sahiron Syamsuddin’s book “Hermeneutics and Development of the Ulumul Qur’an,” among other works. Secondary sources include books and journal articles on hermeneutics, the Qur’an, and classical to modern-contemporary Tafsir literature. These sources are analyzed using descriptive-interpretive methods and historical-philosophical approaches. The findings of this research are twofold: Firstly, Sahiron’s approach aims to contextualize the relevance of the Qur’an in addressing contemporary issues, proposing an interpretive methodology that reconstructs and integrates classical methods with modern approaches, drawing from Western hermeneutic scholars. Secondly, the ma’nā-cum-maghzā methodology is deemed relevant in the current academic milieu for several reasons: it addresses the concerns of progressive Muslim thinkers; it meets the academic demand for evolving Qur’an study methodologies; and its widespread adoption and influence in academic circles in Indonesia, particularly due to its ability to harmonize classical and contemporary interpretations.